2022
DOI: 10.1039/d2cc04912k
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived photoluminescence from an eight-coordinate zirconium(iv) complex with four 2-(2′-pyridyl)pyrrolide ligands

Abstract: The photoluminescent eight-coordinate zirconium complex Zr(HPMPH)4 supported by four monoanionic 2-(2’-pyridine)pyrrolide ligands was synthesized. This molecule shows dual emission via fluorescence and phosphorescence with an overall quantum efficiency of 4%...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the design of effective systems for harnessing and utilizing diffuse solar energy, it is imperative to understand where photoinduced charge-transfer states localize so that they can be extracted to provide electrons for productive redox chemistry. Recent elegant synthesis and spectroscopic studies have shown how to manipulate metal-to-ligand, ligand-to-metal, and ligand-centered charge-transfer states in coordination complexes based on earth-abundant, often first-row transition metals to dramatically extend excited-state lifetimes. The work presented here complements these studies by providing a foundational understanding of the directionality of MLCT states in earth-abundant molecular photosensitizers, potentially circumventing the need for extremely long-lived excited states because the photogenerated electrons are exactly where they need to be. Here, we have shown that by adding common electron-donating or -withdrawing phenanthroline ligands, we can predictively direct the MLCT state to one ligand or another.…”
Section: Discussionmentioning
confidence: 88%
“…In the design of effective systems for harnessing and utilizing diffuse solar energy, it is imperative to understand where photoinduced charge-transfer states localize so that they can be extracted to provide electrons for productive redox chemistry. Recent elegant synthesis and spectroscopic studies have shown how to manipulate metal-to-ligand, ligand-to-metal, and ligand-centered charge-transfer states in coordination complexes based on earth-abundant, often first-row transition metals to dramatically extend excited-state lifetimes. The work presented here complements these studies by providing a foundational understanding of the directionality of MLCT states in earth-abundant molecular photosensitizers, potentially circumventing the need for extremely long-lived excited states because the photogenerated electrons are exactly where they need to be. Here, we have shown that by adding common electron-donating or -withdrawing phenanthroline ligands, we can predictively direct the MLCT state to one ligand or another.…”
Section: Discussionmentioning
confidence: 88%
“…The development of photoactive metal complexes with earth-abundant metals holds great promise to enable sustainable photocatalysis, (solar) energy conversion, and light-emitting diodes (LEDs). Hence, considerable efforts have been undertaken to explore this compound class in the recent years , with creative designs utilizing excited states of different characters like metal-to-ligand charge transfer (MLCT), ligand-to-metal charge transfer (LMCT), ligand-to-ligand charge transfer (LL’CT), and metal-centered (MC) states, , covering zirconium, vanadium, chromium, iron, manganese, cobalt, , copper, molybdenum, and zinc as metal centers , among others.…”
Section: Introductionmentioning
confidence: 99%
“…For an LMCT process to occur, rational selection of electron-deficient metal centers and linkers containing electron-rich functional groups is important. In this regard, on one hand, Zr­(IV) with d 0 electronic configuration has recently gained attention in designing Earth-abundant photoluminescent transition-metal complexes. This is due to the fact that Zr­(IV) is highly electron deficient with no d–d electronic transitions. On the other hand, dihydrotetrazine functions are electron rich due to the presence of two imine −CN– and two −NH sites.…”
Section: Resultsmentioning
confidence: 99%